Patient Safety Program in Emergency Department (ED) at Prof. Dr. Chairuddin Panusunan Lubis Hospital in 2023 - Regina Anastasya Ketaren; Zulfendri Zulfendri; Gerry Silaban (Asian Journal of Social and Humanities, 2023)
This research explores the implementation of patient safety goals in the Emergency Department (ED) of Prof. Dr. Chairuddin Panusunan Lubis Hospital in 2022. Qualitative data gathered from key informants, including the Head of the ED, Head Nurse, and staff nurses, reveals determinants impacting patient safety. The study identifies several findings: good patient identification, the need for improved communication, positive progress in medication safety, effective implementation of site marking, successful reduction of infection risk, and adequate measures to minimize patient falls. Recommendations include enhancing communication among nurses and reinforcing medication safety protocols. The systematic application of site marking ensures precise location and procedures. Efforts to reduce infection risk and prevent patient falls are commendable, supported by appropriate policies, procedures, and training programs